Nosological aspects of hepatomegaly and splenomegaly at pediatric age - M. M. Kotovich; F. K. Manerov; E. V. Luchsheva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate frequency of hepatomegaly and splenomegaly in pediatric patients, to determine their causes and nosological pattern of hepatolienal syndrome (HLS) in relation to age. Material and methods. Overall 5178 children aged 1 month to 17 years were examined to detect hepatosplenomegaly. Frequency of hepatomegaly and/or splenomegaly of unspecified etiology was analyzed with correlation to outpatient clinic admission rate and results of routine inspections. Results. The spectrum of age and main causes of hepatosplenomegaly was studied according to physical examination of 241 children. The most common causes of HLS include infectious diseases - 56 cases (23,2%) and neoplasms - 55 cases (22,8%; p